Improving yield and water productivity of rice in sodic soil with saline water through drip irrigation - RAMESH, THANAKKAN; RATHIKA, S.; Geetha, S.; Sabarinathan, R.; Vijayakumar, S. (ORYZA-An International Journal of Rice, 2024)
A field experiment was conducted at Anbil Dharmalingam Agricultural College and Research Institute, Tiruchirappalli, to determine suitable rice varieties and lateral spacing for drip irrigation in sodic soil with saline water. The experiment involved four short duration rice varieties (’ADT 36’, ’ADT 45’, ’TRY (R) 2’, and ’Anna (R) 4’ ) and four pre-release rice cultures (’TR13-069’, ’TR13-083’, ’TR09-27’, and ’TR09-30’). Drip systems were installed with lateral spacing of 45 cm and 90 cm, and emitter/dripper spacing of 30 cm. Drippers had a discharge rate of 2.0 liters per hour, and irrigation was scheduled at 100% pan evaporation rate, applied every alternate day. The variety, ’’TRY (R) 2’’ produced a greater number of panicles (365/m2) and a higher percentage of tillers to panicles conversion (77%) while ’’ADT 36’’ exhibited a higher number of filled grains (99.5/panicle) and total grains per panicle (117.4). With respect to yield, ’’TRY (R) 2’’ achieved the highest grain yield of 2991 kg/ha, followed by ’’ADT 36’’ and ’’Anna (R) 4 ’’. The drip lateral spacing of 90 cm exhibited significantly higher yield compared to a spacing of 45 cm. The varieties ’’ADT 36’’ and ’’ADT 45’’ utilized 550.3 mm of irrigation water and received 283.5 mm of rainfall, while ’’Anna (R) 4 ’’ and ’’TRY (R) 2’’ used a total of 871.9 mm of water, including 575.2 mm of irrigation water and 296.7 mm of rainfall. Variety ’’TRY (R) 2’’ demonstrated a higher water productivity of 3.58 kg/ha/mm, followed by ’’ADT 36’’. Based on these findings, it is recommended to grow the ’’TRY (R) 2’’ rice variety under drip irrigation with a lateral spacing of 90 cm in sodic soil with saline water conditions, as it showed superior performance in terms of grain yield and water productivity.